A Rolling Stone Gathers No Moss? The Case of Mature Students in Higher Education and Their Plurilingual Repertoires - Susana Ambrósio; Maria Helena Araújo e Sá; Ana Raquel Simões (MDPI AG, 2019)
This study diagnoses how the plurilingual repertoires of mature students (MS) in higher education (HE) are constructed throughout their lives. It addresses the main characteristics of MS; the contexts in which they move throughout their lives, and the situations they contact with languages. Data were collected by means of a questionnaire, mostly comprising open-ended questions. The questionnaire was emailed to 485 MS and was filled in by 195 (40.2%). The results highlight the intrinsic relationship between the MS' life histories and the construction of their plurilingual repertoires. The findings reinforce the relevance of considering the MS' plurilingual repertoires and life histories in the development of educational linguistic policies in HE.